2008
DOI: 10.1159/000137555
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the PPAR-Alpha L162V Polymorphism on the Cardiovascular Disease Risk Factor in Response to n–3 Polyunsaturated Fatty Acids

Abstract: Background: Dietary n–3 polyunsaturated fatty acids (PUFAs) decrease the risk of cardiovascular disease (CVD). Yet, genetic variations of the gene encoding the peroxisome proliferator-activated receptor-α (PPARα) can also modulate CVD risk factors. Since fatty acids, including n–3 PUFAs, are natural ligands of PPARα, a gene-diet interaction effect could be observed. Aims: To examine whether n–3 PUFA- induced changes in CVD risk factors are influenced by the PPARα L162V polymorphism. Methods: Fourteen men, carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 87 publications
1
15
0
1
Order By: Relevance
“…Therefore, the influence of the L162V polymorphic variant may be more apparent in individuals who consume a lower intake of omega-3 FAs. These results are in accordance with previous human studies [10, 11, 21] which examined the effect of the PPAR α L162V polymorphism in relation to diet. These previous researchers determined that a high intake of dietary PUFA can lower TG in carriers of the V162-PPAR α allele [10, 11] due to higher n-3 FA intakes that may lead to increased activation of PPAR α .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, the influence of the L162V polymorphic variant may be more apparent in individuals who consume a lower intake of omega-3 FAs. These results are in accordance with previous human studies [10, 11, 21] which examined the effect of the PPAR α L162V polymorphism in relation to diet. These previous researchers determined that a high intake of dietary PUFA can lower TG in carriers of the V162-PPAR α allele [10, 11] due to higher n-3 FA intakes that may lead to increased activation of PPAR α .…”
Section: Discussionsupporting
confidence: 93%
“…These previous researchers determined that a high intake of dietary PUFA can lower TG in carriers of the V162-PPAR α allele [10, 11] due to higher n-3 FA intakes that may lead to increased activation of PPAR α . Finally, a recent study by Caron-Dorval et al in 2008 [21] demonstrated that plasma TG levels decreased similarly between a group of 28 young men with or without the L162V polymorphism after an intense omega-3 FA supplementation for 4 weeks. These results confirm that dietary modifications including higher amounts of EPA and DHA, which activate PPARs to a greater level, may be an effective method in reducing metabolic risk in those with high-risk allele, such as V162.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic parameters are described in Table 1 with the independent effects of the genotype, the n‐3 PUFA supplementation and interaction between genotype and n‐3 PUFA. Results from blood lipids and dietary intake analysis have been previously published and are discussed elsewhere 30. Briefly, the n‐3 PUFA supplementation was associated with a similar decrease in fasting TG levels in both genotypes, from 1.41 to 1.17 mmol/L (−11.4%, percentage mean of the individual differences) for the L162 homozygotes and from 1.22 to 1.01 mmol/L (−13.1%, percentage mean of the individual differences) for carriers of the PPAR α‐V162 allele.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of significant change in plasma inflammation parameters may be due to genetic variations that influence response to n-3 PUFA supplementation. For example, Caron-Dorval et al (2008) demonstrated an interaction effect between the PPARA L162V polymorphism and n-3 PUFA supplementation for plasma CRP concentrations [28]. Therefore, the effects of polymorphisms on plasma IL6, TNFA and CRP concentrations after n-3 PUFA supplementation should be verified.…”
Section: Discussionmentioning
confidence: 98%